Group layout design of manufacturing cells incorporating assembly and energy aspects. Issue 5 (4th May 2022) - Forghani, Kamran; Fatemi Ghomi, S. M. T.; Kia, Reza
Abstract : Cell Formation (CF) and Group Layout (GL) are two important problems in designing a cellular manufacturing system. This article addresses an integrated CF and GL model as a mixed-integer program, considering energy consumption, assembly aspects and process routing. As a novel feature, machines are assumed to be capable of processing operations with different energy consumption rates and processing times. This model aims to determine concurrently machine cells, the layout of facilities (machines, workstations and cells), process routes and processing speed of operations so that the materials handling cost and the electric energy consumption are minimized. To demonstrate the applicability of the model, managerial insights are provided by a case study. Owing to the computational complexity of the problem, a hybrid solution approach combining a Genetic Algorithm (GA) and Simulated Annealing (SA) is proposed. The computational results demonstrate the superiority of the hybrid approach over CPLEX ® and conventional GAs and SA.